Cerebral microcirculation during mild head injury after a contusion and acceleration experimental model in sheep. (5th December 2016) - Bellapart, Judith; Abi-Fares, Catherine; Cuthbertson, Kylie; Dunster, Kimble; Diab, Sara; Platts, David G.; Raffel, Christopher; Gabrielian, Levon; Barnett, Adrian; Paratz, Jennifer; Boots, Rob; Fraser, John F.
Abstract: Background : Cerebral microcirculation after head injury is heterogeneous and temporally variable. Regions at risk of infarction such as peri-contusional areas are vulnerable to anaemia. However, direct quantification of the cerebral microcirculation is clinically not feasible. This study describes a novel experimental head injury model correlating cerebral microcirculation with histopathology analysis. Objective : To test the hypothesis that cerebral microcirculation at the ischaemic penumbrae is reduced over time when compared with non-injured regions. Methods : Merino sheep were instrumented using a transeptal catheter to inject coded microspheres into the left cardiac atrium, ensuring systemic distribution. After a blunt impact over the left parietal region, cytometric analyses quantified cerebral microcirculation and amyloid precursor protein staining identified axonal injury in pre-defined anatomical regions. A mixed effect regression model assessed the hourly blood flow results during 4 hours after injury. Results : Cerebral microcirculation showed temporal reductions with minimal amyloid staining except for the ipsilateral thalamus and medulla. Conclusion : The spatial heterogeneity and temporal reduction of cerebral microcirculation in ovine models occur early, even after mild head injury, independent of the intracranial pressure and the level of haemoglobin. Alternate approaches to ensure recovery of regions with reversible injury require a targeted assessment of cerebral microcirculation.